If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 6x = -7 Reorder the terms: 6x + 6y = -7 Solving 6x + 6y = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 6x + 6y + -6y = -7 + -6y Combine like terms: 6y + -6y = 0 6x + 0 = -7 + -6y 6x = -7 + -6y Divide each side by '6'. x = -1.166666667 + -1y Simplifying x = -1.166666667 + -1y
| 7+5(x+3)=4x+20 | | 3x-4+5x=10 | | 7+h=12 | | (5/3)^-1 | | 3-5x=8+x | | 2-5t+8+5t-8= | | 13x-5=4(3x+3)-7 | | 6(n-1)=4n+8 | | 3t-3=2t+6 | | 3x+1=x-13 | | x-6=33 | | 6/11-3/11 | | 1=-2/3(x-6) | | X/x-4+8=4/x-4 | | 4(3x-3)-3(2x-4)=0 | | 1=-2/3(x-1/6) | | X+3(5+3x)=95 | | 64x^2-112x=0 | | 3/8+5/12 | | (4x+5)(x^2+2x-8)=0 | | .24(57.5)+.17y=17.8 | | 3x+6.84=2x | | -7+-24= | | 3/10-1/4 | | 29-(x+6)=9x-7 | | 3r+8=20 | | 4*(x+2)=18 | | -17=p+3-3p | | 9y-12-4y+9=0 | | 12+9x-6x-19= | | c(c-5)=14 | | 8y-14-4y+9=0 |